2021
DOI: 10.1108/par-12-2020-0209
|View full text |Cite
|
Sign up to set email alerts
|

The effects of state ownership and tax rate cuts on accounting conservatism: evidence from Vietnam

Abstract: Purpose The purpose of this paper is to examine the joint effects of state ownership and tax rate cuts on accounting conservatism, considering the different levels of foreign ownership in the context of Vietnam. Design/methodology/approach The paper uses ordinary least squares regressions and a data set of 405 firms covering the period 2007 to 2019. The manuscript uses three measures of accounting conservatism: Basu’s 1997 timeliness of earnings, Basu’s 1997 earnings persistence and the book-to-market ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…Moreover, Taing & Chang (2021) use the Theory of Planned Behavior (TPB) to understand the behavior of Phnom Penh's citizens in complying with their tax obligation and find that tax morale, tax fairness, and tax complexity have influenced the intention to pay tax. Le & Moore (2021) also use TPB to analyze the electronic tax compliance of small and medium enterprises (SMEs) in Vietnam and find that the most influencing factor to increase tax compliance is taxpayer awareness. The Vietnamese government should pay attention to promoting and supporting SMEs to raise their tax obligation awareness.…”
Section: Tax Compliancementioning
confidence: 99%
“…Moreover, Taing & Chang (2021) use the Theory of Planned Behavior (TPB) to understand the behavior of Phnom Penh's citizens in complying with their tax obligation and find that tax morale, tax fairness, and tax complexity have influenced the intention to pay tax. Le & Moore (2021) also use TPB to analyze the electronic tax compliance of small and medium enterprises (SMEs) in Vietnam and find that the most influencing factor to increase tax compliance is taxpayer awareness. The Vietnamese government should pay attention to promoting and supporting SMEs to raise their tax obligation awareness.…”
Section: Tax Compliancementioning
confidence: 99%
“…Vietnam is a transitional economy with low financial reporting disclosure standards (Blenman and Le, 2014), low market efficiency (Gupta et al , 2014) and limited alternative sources of external capital (Le, 2019). Ownership structure and capital access are unique in Vietnam, where the government and foreign investors are key market participants (Le and Moore, 2023, 2022). Firms with high government or foreign ownership have easier access to capital, and therefore, lower motivation to manage earnings.…”
Section: Introductionmentioning
confidence: 99%
“…Managers will choose policies that minimize the tax expenses so that the company's profit increases. Thus, to benefit from the tax rate reduction, firms will try to shift taxable income to the year when the rate is lower (Le & Moore, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…So it can be concluded that managers will try to maximize their level of tax avoidance by changing their policies following changes in policies related to corporate taxation. As stated by previous research, to optimize the level of tax avoidance when dealing with regulations that affect tax avoidance strategies, companies must develop other strategies (Kim et al, 2019) Figure 1 Source: Agency Theory-Tax Avoidance Framework (Wilde & Wilson, 2018) Companies may engage in or intensify tax avoidance as a result of reduced corporate income tax rates (Le & Moore, 2022). And shifting profits to years with lower corporate income tax rates is one of the tax avoidance strategies (Le & Moore, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation